Hesperidin Interacts With CREB-BDNF Signaling Pathway to Suppress Pentylenetetrazole-Induced Convulsions in Zebrafish - Sharma, Pallavi; Kumari, Savita; Sharma, Jatin; Purohit, Rituraj; Singh, Damanpreet (Frontiers in Pharmacology, 2021)
Hesperidin (3,5,7-trihydroxyflavanone 7- rhamnoglucoside) is a β-7-rutinoside of hesperetin (4'-methoxy-3',5,7-trihydroxyflavanone), abundantly found in citrus fruits and known to interact with various cellular pathways to show a variety of pharmacological effects. The present study envisaged to understand the anticonvulsant effect of hesperidin in a zebrafish model of pentylenetetrazol (PTZ)-induced convulsions, with the support of in silico docking. Healthy zebrafish larvae were preincubated with hesperidin (1 µM, 5 µM and 10 µM) for 1 h, before PTZ exposure. Hesperidin treatment significantly increased the seizure latency and minimized PTZ-induced hyperactive responses. A significant reduction in c-fos expression further supported the suppression of neuronal excitation following hesperidin incubation in the larvae exposed to PTZ. The treatment also modulated larval bdnf expression and reduced the expression of il-10. The results of in vivo studies were further supported by in silico docking analysis, which showed the affinity of hesperidin for the N-methyl-D-aspartate receptor, the gamma-aminobutyric acid receptor, Interleukin 10 and the TrkB receptor of brain-derived neurotrophic factor. The results concluded that hesperidin suppresses PTZ-mediated seizure in zebrafish larva through interaction with the central CREB-BDNF pathway.